Майкл Фарадей и его научные заслуги перед человечеством - Баранов, Михаил Иванович (НТУ "ХПИ", 2009)
Приведен краткий очерк из всемирной истории электричества об основных фундаментальных достижениях великого английского физика Майкла Фарадея в области электромагнетизма.

A brief outline from the history of electricity is given on the main fundamental achievements of the great English physicist Michael Faraday in field of electromagnetism.
Michael Faraday and his scientific accomplishments in the face of humanity
Keywords: электричество; магнетизм; электромагнитная индукция; физический эксперимент; ученые физики; Фарадей Майкл; magnetism; physical experiment; electromagnetic induction; outline; electricity